Synthesis of algorithms for stabilization ofthe level of inter-operative backlogs of the production flow line - Pihnastyi, O. M.; Khodusov, V. D. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The report discusses methods for constructing algorithms for optimal stabilization of the value of inter-operational backlogs of the production flow line.
Keywords: production line; PDE-model of production; PDE-model; flow production